2016
DOI: 10.1038/eye.2016.142
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of subthreshold micropulse laser (577 nm) treatment and half-dose photodynamic therapy in patients with chronic central serous chorioretinopathy

Abstract: Purpose To compare the short-term treatment outcome of the 577 nm subthreshold micropulse laser (SML) and half-dose photodynamic therapy (PDT) in patients with chronic central serous chorioretinopathy (cCSC) and persistent subretinal fluid (SRF). Methods This retrospective study included 100 eyes of 100 consecutive patients who were treated with the 577 nm SML (Supra Scan, Quantel Medical) (n = 42) or half-dose PDT (n = 58) for cCSC. The treatment was applied at the leakage sites in the fluorescein and indocya… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(49 citation statements)
references
References 31 publications
2
42
0
5
Order By: Relevance
“…Scholz et al also performed a retrospective comparative study with 577 nm yellow microuplse NRT, comparing it against half-dose PDT in 100 patients with chronic CSCR. 59 Six weeks after treatment, both groups had a statistically significant decrease in CMT (−148µm, NRT; −76µm, PDT) with 36% of eyes in the NRT group showing complete resolution of fluid as compared to 21% in the PDT group. Kretz et al performed a prospective randomized control study that compared SDM with half-dose PDT and observational control among 62 chronic CSCR patients.…”
Section: Management Of Chronic Diseasementioning
confidence: 89%
“…Scholz et al also performed a retrospective comparative study with 577 nm yellow microuplse NRT, comparing it against half-dose PDT in 100 patients with chronic CSCR. 59 Six weeks after treatment, both groups had a statistically significant decrease in CMT (−148µm, NRT; −76µm, PDT) with 36% of eyes in the NRT group showing complete resolution of fluid as compared to 21% in the PDT group. Kretz et al performed a prospective randomized control study that compared SDM with half-dose PDT and observational control among 62 chronic CSCR patients.…”
Section: Management Of Chronic Diseasementioning
confidence: 89%
“…In a similar study to ours, Scholz and colleagues13 compared the short-term outcomes of eyes treated with yellow MP laser with eyes treated with half-dose PDT. They reported that at 6 weeks, both half-dose PDT and yellow MP laser were effective for chronic CSCR.…”
Section: Discussionmentioning
confidence: 79%
“…Our results in general were much more favourable in both the MP laser and PDT arms. The patients in the series of Scholz et al 13 had a mean duration of disease of 4 years.…”
Section: Discussionmentioning
confidence: 97%
“…[28,29] Those inconsistences may be a consequence of different characteristics of the study groups, especially in regard to the duration of the disease and baseline visual acuity. Studies directly comparing SMPLT and PDT in the treatment of chronic CSCR generally do not favor any of these therapies and reveal moderate BCVA improvement (a few ETDRS letters) similar in both groups [30,31,32]. Only large PLACE trial shows significantly better morphological results with PDT treatment and moderately better visual outcome compared to SMPLT ( + 6.78 ETDRS letters versus +4.48 ETDRS letters at 7 months).…”
Section: Discussionmentioning
confidence: 98%